Pharmacokinetics of prolonged‐release tacrolimus versus immediate‐release tacrolimus in de novo liver transplantation: A randomized phase III substudy. Issue 6 (27th April 2017) - Ericzon, Bo‐Göran; Varo, Evaristo; Trunečka, Pavel; Fischer, Lutz; Colledan, Michele; Gridelli, Bruno; Valdivieso, Andrés; O'Grady, John; Dickinson, James; Undre, Nasrullah
Abstract: Background: With the same dose of tacrolimus, lower systemic exposure on the first day of dosing has been reported for prolonged‐release tacrolimus compared with immediate‐release tacrolimus, prompting investigation of differing initial doses. Methods: This substudy of a double‐blind, randomized, phase III trial in de novo liver transplant recipients compared the pharmacokinetics of once‐daily prolonged‐release tacrolimus (initial dose: 0.2 mg/kg/day) versus twice‐daily immediate‐release tacrolimus (initial dose: 0.1 mg/kg/day) during the first 2 weeks post‐transplant. Results: Pharmacokinetic data were analyzed from patients receiving prolonged‐release tacrolimus (n=13) and immediate‐release tacrolimus (n=12). Mean systemic exposure (AUC0‐24 ) was higher with prolonged‐release versus immediate‐release tacrolimus. Dose‐normalized AUC0‐24 (normalized to 0.1 mg/kg/day) showed generally lower exposure with prolonged‐release tacrolimus versus immediate‐release tacrolimus. There was good correlation between AUC0‐24 and concentration at 24 hours after the morning dose ( r =.96 and r =.86, respectively), and the slope of the line of best fit was similar for both formulations. Conclusions: Doubling the initial starting dose of prolonged‐release tacrolimus compared with immediate‐release tacrolimus overcompensated for lower exposure on Day 1. A 50% higher starting dose of prolonged‐release tacrolimus than immediate‐release tacrolimus may be required for similar systemic exposure. However, doses of both formulations can be optimized using the same trough‐level monitoring system. (ClinicalTrials.gov number: NCT00189826).